Webtoon sebagai Inovasi Media Pembelajaran Sejarah Kebudayaan Islam untuk Meningkatkan Motivasi Belajar Siswa Kelas V Madrasah Ibtidaiya - Moh Ali Fauzi; Luluk Indarinul Mufidah (IERA, Islamic Education and Research Academy, 2025)
This research aims to develop, test the validity, and evaluate the effectiveness of Webtoon as an innovative learning medium for Islamic Cultural History subject, specifically on the "Causes and Events of Fathu Makkah" material for fifth-grade students at MI Islamiyah Lengkong Nganjuk. Using the Research and Development (R&D) method with the 4D model (Define, Design, Develop, Disseminate), this study produced a digital comic titled "Study With Aza" consisting of six episodes. The product was validated by media experts, material experts, and language experts, and tested on 28 students and 5 teachers. The results showed that the Webtoon media was deemed very valid by media experts (86%), material experts (94%), and language experts (98%). Teacher responses reached 82% (Very Good), and student responses averaged 85% (Very Good). This indicates that Webtoon is a valid, practical, and effective medium that can increase learning motivation and facilitate understanding of Islamic Cultural History material. This research implies that Webtoon can be an innovative alternative learning medium that is relevant to the characteristics of elementary school students in the digital era